Liver Involvement in Children during the Diagnosis of Celiac Disease: A Single-Center Experience from Turkey - Altay, Derya; Doğan, Yaşar (Shiraz University of Medical Sciences, 2022)
BACKGROUND: Liver abnormalities in Celiac disease (CD) are common. The aim of this study was to investigate the children with CD who were followed up in our clinic presenting with elevated aminotransferase levels. METHODS: In this study, the data of 419 pediatric patients with CD were retrospectively analyzed, and those with elevated aminotransferase levels during the diagnosis of CD were assessed. RESULTS: Elevation of aminotransferase levels was found in 66 (15.7%) patients among the 419 patients during the diagnosis of CD. The mean age of these patients was 7.33±3.96 years. Liver enzymes were mildly elevated in 63 (95.4%) patients. However, half of the patients with elevated liver enzymes had a 1.25-fold increase in aminotransferase levels. Patients with hypertransaminasemia had higher weight loss and lower folic acid values compared with patients with normal liver enzymes. Patients’ liver tests were reverted to normal, except for two patients with chronic liver disease, after 9.27±3.16 months of administering a gluten-free diet. CONCLUSION: Patients with liver involvement should be investigated for CD. Especially, mildly elevation of aminotransferase levels should be taken into account by pediatricians for Celiac hepatitis. © 2022 The Author(s).
Keywords: Aminotransferase levels; Celiac disease; Pediatric